AB0441 Effectiveness of Tocilizumab in Monotherapy in Patients with Rheumatoid Arthritis in Clinical Practice. (9th June 2015) - Magallares, B.; Quesada-Masachs, E.; Hernández, M.; Lisbona, M.; Moya, P.; Moreno, M.; Torrente-Segarra, V.; Reina, D.; Narváez, J.; Marsal, S.; Sanmartí, R.; Calvet, J.; et al.
Abstract : Background: There are few data about Tocilizumab (TCZ) in monotherapy effectiveness in clinical practice conditions Objectives: To analyze the effectiveness TCZ monotherapy at medium/long term in clinical practice Methods: Observational, retrospective, multicenter, 2-year study of RA patients on TCZ monotherapy.We recorded: demographic and clinical data (duration of RA, RF and CCP antibodies, previous treatments and reason for its discontinuation); At baseline and at 3, 6, 9, 12, 18 and 24 months:RA activity (DAS-28 ESR index, TJC, SJC, ESR, CRP and % of patients in Remission or Low Disease Activity (LDA). Adverse effects were also recorded Results: 123 patients were included, with a mean age of 57.7±12.5 years and 85.4% females. Mean disease duration of 14.4±12.0 y; 67.5% and 59'3% were RF and anti-CCP positive. 98.4% had previously received conventional DMARD (2 DMARDs: 30.9% and ≥3 DMARDs: 38.2%), reasons for DMARD discontinuation were inefficacy (26%), adverse events (58.5), patient decision (8.9%) and other reasons (4.1%). 13% had not received prior biological DMARDs; 34.1% had received 1; 20.3% 2; 16.3% 3; 8.9% 4 and 6.5% ≥5) A relationship between Remission/LDA and disease duration and reason for discontinuation of prior conventional DMARD was not found. An association among the number of previous biological treatments and a low disease activity at 6 m (p<0.017), 9m (p<0.025) and 12m (p<0.028) was observed. 41 patients discontinued treatment (33.3%): 17due to inefficacy, 13 due to AE, 4 because of patient decision and 7 due to other reasons. No association between discontinuation of TCZ and duration of disease or number of previous biological DMARDs was found. Conclusions: In our experience, TCZ monotherapy is effective at medium/long term regardless of the duration of the disease and previous treatments, maintaining a high retention rate Disclosure of Interest: None declared